8x+6x-20=60-6x

Simple and best practice solution for 8x+6x-20=60-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+6x-20=60-6x equation:


Simplifying
8x + 6x + -20 = 60 + -6x

Reorder the terms:
-20 + 8x + 6x = 60 + -6x

Combine like terms: 8x + 6x = 14x
-20 + 14x = 60 + -6x

Solving
-20 + 14x = 60 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-20 + 14x + 6x = 60 + -6x + 6x

Combine like terms: 14x + 6x = 20x
-20 + 20x = 60 + -6x + 6x

Combine like terms: -6x + 6x = 0
-20 + 20x = 60 + 0
-20 + 20x = 60

Add '20' to each side of the equation.
-20 + 20 + 20x = 60 + 20

Combine like terms: -20 + 20 = 0
0 + 20x = 60 + 20
20x = 60 + 20

Combine like terms: 60 + 20 = 80
20x = 80

Divide each side by '20'.
x = 4

Simplifying
x = 4

See similar equations:

| 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 | | 8=0.25(-m-1) | | 3(-3+2x)=9 | | 3m+n=35 | | 3(x+1)+2(2x-6)=33 | | 3x^3+2x^2+-41x+-66=0 | | 8a-48=-6(-6-6a) | | 6(2-3x)=4(5x+7) | | 2(5*555*5)-56= | | 5y+60-9=12+8y-72 | | 200*50+20= | | 9m+5=9m+6 | | m=n-7 | | -34m=12 | | 2x-9y=-3 | | 0=12x+4.9x^2 | | 90-6x=100-8x | | 2(6x-6)+3=2(2x+3)+5 | | 8x-4=10x+19 | | 9xz^2-30xz-96x= | | -2x-7(c+3)=-93 | | 1(a-4)=2(2a+4) | | 8x-4=10+19 | | 4-3yi=4x+16i | | -329=-7(7+5p) | | x=0.5+y | | 3(4x-7)=6-(2-5x) | | 8(-8k-1)=5k-8 | | -11=9-2b | | 31=25-x-x |

Equations solver categories